2018
DOI: 10.1002/ecs2.2353
|View full text |Cite
|
Sign up to set email alerts
|

Responses of non‐native earthworms to experimental eradication of garlic mustard and implications for native vegetation

Abstract: Recent studies in invasion biology suggest that positive feedback among two or more introduced organisms facilitate establishment within a new range and drive changes in native plant communities. Here, we experimentally tested for relationships between native plants and two non‐native organisms invading forest habitats in North America: garlic mustard (Alliaria petiolata, Brassicaceae) and earthworms. In two forested sites, we compared understory vegetation and earthworm biomass in plots where garlic mustard w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…Most populations were found on the crest of or along mild slopped hills. In all the sites, we found signs of Lumbricus terrestris invasion, which was expected since the removal of A. petiolata has been shown to reduce L. terrestris densities (Stinson et al 2018).…”
Section: Methodsmentioning
confidence: 52%
“…Most populations were found on the crest of or along mild slopped hills. In all the sites, we found signs of Lumbricus terrestris invasion, which was expected since the removal of A. petiolata has been shown to reduce L. terrestris densities (Stinson et al 2018).…”
Section: Methodsmentioning
confidence: 52%
“…Soil micronutrients (e.g., copper, iron, manganese, zinc, and sodium) have not been associated with garlic mustard success, although they have been measured in few studies (Lankau 2012a , Anderson et al 2019 ). Garlic mustard was positively associated with higher soil moisture at regional scales (Haines et al 2018 ), but other studies showed no effect of garlic mustard on soil moisture up to 8 years after removal (Stinson et al 2018 , Burke et al 2019 ). In summary, the complexity and variability of findings for garlic mustard interactions with soil suggest a need to investigate the scales at which garlic mustard associates with elevated nutrient levels and other soil characteristics.…”
Section: Mechanisms For Garlic Mustard Invasion Success Across Ecolog...mentioning
confidence: 99%
“…Earthworms, as ecosystem engineers, have broad-reaching effects on ecosystems (Le Bayon et al 2017 ), but their role in facilitating the expansion of garlic mustard is unclear. In general, nonnative earthworm biomass is positively associated with invasive plant cover (including garlic mustard) and negatively associated with native plant presence (Nuzzo et al, 2009 , 2015 , Craven et al 2017 ), and removal of garlic mustard decreases nonnative earthworm biomass (Stinson et al 2018 ). However, Hopfensperger and Hamilton ( 2015 ) found a negative relationship between garlic mustard cover and the proportion of immature nonnative earthworms, which they speculated may be associated with allelopathy.…”
Section: Mechanisms For Garlic Mustard Invasion Success Across Ecolog...mentioning
confidence: 99%
See 1 more Smart Citation